Atenção secundária em saúde bucal em municípios de pequeno porte: uma avaliação transversal da demanda x acesso - Wellen Carla da Luz Benfica (2017)
The oral Health National Policy aims at ensuring the right to access and integrality to the oral health care organizing itself through the care network.However, despite the improvement to the access to procedures of Primary Care, the implementation of the Dental Specialties Centers is slow, unequal and the attendance voids seen still define the lack or difficulty in accessing specialized procedures in oral health limiting the care integrality. The present study aims at acknowledging the demands and the access to specialized procedures in Oral Health within 10 towns in the area of Guanhães, Minas Gerais, which do not have Dental Specialties Centers. In a transversal design, the research was performed with 30 Dental Surgeons (DS) of Primary Care who recorded all the patients treated between July and November 2016 who presented the need of being assigned to specialized procedures in oral health. The descriptive analysis was developed with the software SPSS for Windows version 18.0. The population in this region consists of 99.245 inhabitants; the average of the Municipal Human Development Index is 0,618, the medium income per person is of R$ 346,96 and the illiteracy rate for subjects above the age of 15 years old is of 19%. The coverage of the Family Health Strategy is of 98,75% and of the Oral Health, 94%. The study was approved by the Ethics in Research Committee of the Federal University of Minas Gerais (ruling 1.615.701). 1085 patients were identified for having presented the need of being assigned to specialized procedures in Oral Health. Most of them were females (56,6%), with an age range of 13-34 years old (52,6%). Among the specialties analyzed, 61% of the patients needed endodontic treatment, the most compromised tooth was the first permanent molar (26,4%) in patients ranging from 13-34 years old (64,2%). The need for a prosthesis was observed in 22,9% of the patients. Among the 836 patients effectively assigned, 96,6% were referred to the private sector. The outcomes were recorded for 435 patients, of those 19,8% of the procedures were performed in the very health unit and 45,5% of the patients were subjected to dental extraction. The data found show a high demand for the endodontic specialty. Without the option of access to specialized treatment in the public sector (lack of CEO), several patients referred to this specialty had their teeth extracted.The absence of recordings of the outcome of the majority of the patients highlights that the primary care in oral health of the region is limited within its role of coordinating the care and guiding the network. In order to have the Oral Health National Policy contemplating the specificities of such regions, it is suggested that the scope of action of the oral health teams in the primary care are expanded or that less expensive specialized services are created, so that the access to this level in oral health is assured to all referred patients.